Angiosperm-like pollen and Afropollis from the Middle Triassic (Anisian) of the Germanic Basin (Northern Switzerland) - Hochuli, Peter A.; Feist-Burkhardt, Susanne (Frontiers in Plant Science, 2013)
Here we report on angiosperm-like pollen and Afropollis from the Anisian (Middle Triassic, 247.2 – 242.0 Ma) of a mid-latitudinal site in Northern Switzerland. Small monosulcate pollen grains with typical reticulate (semitectate) sculpture, columellate structure of the sexine and thin nexine show close similarities to early angiosperm pollen known from the Early Cretaceous. However, they differ in their extremely thin inner layer (nexine). Six different pollen types (I-VI) are differentiated based on size, reticulation pattern and exine structure. The described pollen grains show all the essential features of angiosperm pollen. However, considering the lack of a continuous record throughout the lower part of the Mesozoic and the comparison with the oldest Cretaceous finds we suggest an affinity to an angiosperm stem group. Together with the previously published records from the Middle Triassic of the Barents Sea area the angiosperm-like pollen grains reflect a considerable diversity of the parent plants during the Middle Triassic. Sedimentological evidence and associated palynofloras also suggest a remarkable ecological range for these plants. Associated with these grains we found pollen comparable to the genus Afropollis. Representatives of this genus are commonly recorded in Lower Cretaceous sediments of low latitudes, but until now had no record from the lower part of the Mesozoic.